A severe case of systemic lupus erythematosus with increased pressure communicating hydrocephalus - TUNCER, EMİNE NEŞE; DİRESKENELİ, RAFİ HANER; TUĞLULAR, ZÜBEYDE SERHAN (AVES, 2015)
Normal/increased pressure hydrocephaly is an unusual manifestation of systemic lupus erythematosus (SLE), and the pathogenesis is still unclear. We report the case of an 18-year-old white female with severe refractory renal and pulmonary involvement who developed stupor during intensive immunosuppressive treatment. Enlarged ventricles on imaging and increased intracranial pressure with the exclusion of infectious and hemorrhagic/thrombotic processes suggested increased pressure communicating hydrocephalus associated with SLE. Few case reports are reviewed, and potential pathophysiologic mechanisms are discussed.
Keywords: Hydrocephalus; increased pressure communicating; systemic lupus erythematosus